2019
DOI: 10.1097/md.0000000000016552
|View full text |Cite
|
Sign up to set email alerts
|

Is pharmacological anticoagulant prophylaxis necessary for adolescent idiopathic scoliosis surgery?

Abstract: We report the outcomes of mechanical prophylaxis and chemoprophylaxis in patients who underwent elective surgery for idiopathic adolescent scoliosis (AIS). We retrospectively studied the patients who underwent posterior spinal instrumentation for AIS. The patients were divided into three groups: Group A low-molecular-weight heparin (LMWH) started at 8 hours after surgery; Group B LMWH started at 24 hr after surgery; Group C did not receive chemoprophylaxis. The data about wound oozing, need for tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 19 publications
0
19
1
Order By: Relevance
“…Generally, the use of deep venous thrombosis (DVT) chemoprophylaxis is not common in AIS surgery, as the use of antiembolic stockings and early mobilization have been known to be effective. [29][30][31] Prior literature even suggests that pharmacological prophylaxis after elective spine surgery does not significantly reduce the risk of DVT or pulmonary embolism but instead increases the rate of postoperative hematoma. 32 In this study, compared with patients without DVT chemoprophylaxis, patient use of anticoagulation increased the rates of perioperative blood transfusion (40% vs 31.3%), postoperative hematoma (5.5% vs 1.2%), and readmission (32.7% vs 4.1%) within 90 days.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the use of deep venous thrombosis (DVT) chemoprophylaxis is not common in AIS surgery, as the use of antiembolic stockings and early mobilization have been known to be effective. [29][30][31] Prior literature even suggests that pharmacological prophylaxis after elective spine surgery does not significantly reduce the risk of DVT or pulmonary embolism but instead increases the rate of postoperative hematoma. 32 In this study, compared with patients without DVT chemoprophylaxis, patient use of anticoagulation increased the rates of perioperative blood transfusion (40% vs 31.3%), postoperative hematoma (5.5% vs 1.2%), and readmission (32.7% vs 4.1%) within 90 days.…”
Section: Discussionmentioning
confidence: 99%
“…Length of stay was significantly shorter in the non-chemoprophylaxis group. The authors did not find a correlation between when chemoprophylaxis was initiated and the reported complications 228 .…”
Section: - Should Pediatric Patients Undergoing Major Spine Procedure...mentioning
confidence: 84%
“…Finally, 10 studies were included in the review after full text screening. [25][26][27][28][29][30][31][32][33][34][35] Of the 10 included studies, two were randomized control trials (RCT), 26,27 seven were cohort studies, 25,[28][29][30][31][32][33] and one was a case-control study. 34 Regarding the quality assessment rating, three studies rated good, 27,28,34 four rated fair, 25,26,31,32 while three studies rated poor.…”
Section: Included Studiesmentioning
confidence: 99%
“…34 Regarding the quality assessment rating, three studies rated good, 27,28,34 four rated fair, 25,26,31,32 while three studies rated poor. 29,30,33 We divided the studies into three categories based on the population studied: (1) children admitted to the intensive care unit (ICU), 25,26 (2) children with fractures and/or undergoing surgery, [28][29][30][31]34 and (3) children with systemic disease, for example, congenital heart disease or cancer. 27,32,33 Characteristics and results of the included studies are presented in ►Table 1.…”
Section: Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation